Peningkatan Keterampilan Membaca Permulaan Siswa Dengan Menerapkan Metode Multisensori Berbasis Media Kartu Kata Bergambar - Inda; Ummah BK, Muh. Khaerul; Wukungsenggo, Yolpi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low beginning reading skills of second-grade students at SDN 4 Nalu. The objective of this study was to improve students' beginning reading skills by applying a multisensory method based on picture word card media. The research method used was Classroom Action Research (CAR), which was conducted in two cycles. The research subjects were 24 second-grade students at SDN 4 Nalu. Data collection techniques included observation, interviews, tests, and documentation. The results showed a significant improvement in students' beginning reading skills. In Cycle I, the percentage of students who achieved learning mastery was 4.1% in the first meeting, 16.6% in the second, and 20.8% in the third. After reflective improvements were made for the next cycle, the learning outcomes in Cycle II increased significantly, with the students' mastery percentage reaching 91.6%. Based on these results, it can be concluded that the application of the multisensory method with picture word card media was successful in enhancing the beginning reading skills of the students.